Themes in comparative law - Birks, Peter (Oxford University Press, 2002)
Compiled in honor of Bernard Rudden, this is a book of essays in comparative law centering on the contribution which comparative analysis can make to the core subjects of private law, namely property and obligations. The essays are contributed by leading academics from all over the world, all of whom owe an intellectual debt to the honorand